Hubungan Nilai-Nilai Pribadi Pengusaha, Strategi Bisnis terhadap Kinerja Pengrajin Sasirangan di Banjarmasin - Dwi Wahyu Artiningsih (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The maker of Sasirangan has an important role in the growth of economy in that we are interested in conducting further study to compare those producers who have entrepreneurship quality compared to those conservatives. The second purpose of the research is to identify the performance differences between those who are proactive in implementing their business strategy and those who are reactive.The research involves 35 respondents, by using census sampling techniques and data are analyzed by using cluster analysis and different test by using ANOVA.Base on the result, the producers who are proactive shows better performance than those conservatives who are only implementing reactive strategy.The implication of this research is that Sasirangan makers need to have entrepreneurship spirit and be more creative in designing the pattern and color as well as implementing appropriate strategy.Keywords: Business Strategy and Performance